The main trends in the field of optimization of the regulation system: world experience - Kurmanalina, А.; Gusmanova, Zh. (BUKETOV BUSINESS REVIEW, 2019)
In the article a comparative description of banking regulation, as well as the regulatory characteristic of regulatory and supervisory functions of the state in the sphere of banking activity are given. Methods and tools of banking regulation and supervision are considered. The classification model, interrelation of methods and monetary regulation tools in the author's edition are given. The role and importance of innovations in the development of the country's economy is studied. The features of the the state innovation policy in modern conditions, the main factors influencing it were studied. The characteristic of the main factors and types of innovation policy are given. Experience of innovative activity regulation on the example of the European Union, Japan and the USA is considered. The main characteristics of innovation policy on the example of developed countries with the identification of the main specific features and characteristics are studied. The comparative characteristic of the state bodies of supervision in the sphere of banking innovations, their distinctive features are given. The types of innovation policy and the role of the state in stimulating and regulating innovation are considered. The role of the state and state institutions in regulation and stimulation of innovations is revealed. Based on the analysis of the current state of banking supervision in the world economic space, certain conclusions were made and specific recommendations were proposed.